If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5a + -2b + 8ab + 9) + -1(2a + b + 8ab + -1) = 0 Reorder the terms: (9 + 5a + 8ab + -2b) + -1(2a + b + 8ab + -1) = 0 Remove parenthesis around (9 + 5a + 8ab + -2b) 9 + 5a + 8ab + -2b + -1(2a + b + 8ab + -1) = 0 Reorder the terms: 9 + 5a + 8ab + -2b + -1(-1 + 2a + 8ab + b) = 0 9 + 5a + 8ab + -2b + (-1 * -1 + 2a * -1 + 8ab * -1 + b * -1) = 0 9 + 5a + 8ab + -2b + (1 + -2a + -8ab + -1b) = 0 Reorder the terms: 9 + 1 + 5a + -2a + 8ab + -8ab + -2b + -1b = 0 Combine like terms: 9 + 1 = 10 10 + 5a + -2a + 8ab + -8ab + -2b + -1b = 0 Combine like terms: 5a + -2a = 3a 10 + 3a + 8ab + -8ab + -2b + -1b = 0 Combine like terms: 8ab + -8ab = 0 10 + 3a + 0 + -2b + -1b = 0 10 + 3a + -2b + -1b = 0 Combine like terms: -2b + -1b = -3b 10 + 3a + -3b = 0 Solving 10 + 3a + -3b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + 3a + -10 + -3b = 0 + -10 Reorder the terms: 10 + -10 + 3a + -3b = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 3a + -3b = 0 + -10 3a + -3b = 0 + -10 Combine like terms: 0 + -10 = -10 3a + -3b = -10 Add '3b' to each side of the equation. 3a + -3b + 3b = -10 + 3b Combine like terms: -3b + 3b = 0 3a + 0 = -10 + 3b 3a = -10 + 3b Divide each side by '3'. a = -3.333333333 + b Simplifying a = -3.333333333 + b
| 2x-5/-2=-10 | | -3x+23y=-11 | | 2x^2-px+16=0 | | 14=-7/2x | | -16x^2+64x+4=0 | | 24=4/3w | | x^3+9x^2-7x-10=0 | | -1/6X-1/5X | | 3xsquared-48= | | 0.5x^2+50x-5000=0 | | x+4.33=6.26 | | 1/6X-1/5X | | 4x^2+12x+9=72+x^2 | | y-1/8=-3/4 | | tan(3x)=0.9 | | x-((x^3-2x^2-5)/(3x^2-4x)) | | 4y-3(y-6)+2=6 | | 12^(3/5)= | | 3000-15x=3500-25x | | 3500-25x=3000-15x | | D(ln8x)/Dx= | | 2.3=2X+X | | Y-58=-43 | | x+y+x=30 | | 86*5*2=x | | 86*5*2= | | (x*5)*2=1444 | | 22x=18x+12 | | -2=v+3 | | 12+18x=22x | | x+x+(x-24)=90 | | xsquared-4x-45=0 |